An Examination of the Association of Distress Intolerance and Emotion Regulation with Avoidance - McHugh, R. Kathryn (Cognit Ther Res, 2012)
Distress intolerance is an important motivator of maladaptive avoidance-based coping strategies. The selection of such avoidance behaviors is also influenced by one’s access to alternative emotion regulatory strategies. However, little research has examined the relative contributions of these vulnerability factors to avoidance. This study examined whether distress intolerance and access to emotion regulation strategies were uniquely (additively or interactively) associated with self-reported avoidance. Two samples—an unselected sample (n = 300) and a clinical sample (n = 100)—comprised of patients seeking treatment for unipolar mood and/or anxiety disorders were administered measures of distress intolerance, emotion regulation, and avoidance. Results of linear regression analyses indicated that distress intolerance and access to emotion regulation strategies were uniquely and additively associated with avoidance. Implications for the prevention and treatment of psychological disorders are discussed.